2007
DOI: 10.1021/ie0612008
|View full text |Cite
|
Sign up to set email alerts
|

N2O Decomposition over Perovskite Catalysts

Abstract: Four perovskite catalysts LaBO3 (where B = Cr, Mn, Fe, and Co) were prepared via a highly exothermic and self-sustaining reaction, the so-called “solution combustion synthesis (SCS)”, and characterized by means of X-ray diffraction, BET, field-emission scanning electron microscopy−energy-dispersive spectrometry, and H2-temperature-programmed reduction (TPR) analyses. The performance of these catalysts toward the decomposition of N2O to N2 and O2 was evaluated in a temperature programmed reaction (TPRe) apparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 23 publications
5
83
0
4
Order By: Relevance
“…In each test, 0.10 g catalyst (sieve fraction: 0.25-0.5 mm) was placed into a quartz reactor (4 mm i.d.) and pretreated in He at 600 8C for 1 h. After the reactor was cooled down to 200 8C, the reactant gas mixture (N 2 O, CH 4 and other gases, He balance) was fed into the catalytic reactor with the total flow rate at 60 ml min À1 , i.e. GHSV = $30,000 h À1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In each test, 0.10 g catalyst (sieve fraction: 0.25-0.5 mm) was placed into a quartz reactor (4 mm i.d.) and pretreated in He at 600 8C for 1 h. After the reactor was cooled down to 200 8C, the reactant gas mixture (N 2 O, CH 4 and other gases, He balance) was fed into the catalytic reactor with the total flow rate at 60 ml min À1 , i.e. GHSV = $30,000 h À1 .…”
Section: Methodsmentioning
confidence: 99%
“…Although most zeolite catalysts suffer the activity loss during the operation under these practical conditions, we have luckily found that Fe-USY zeolite shows a high activity and a high hydrothermal stability for N 2 O decomposition in our previous studies under the similar conditions [11,12]. Therefore, the objective of this paper was to examine the catalytic behaviors of N 2 O-CH 4 4 -derived intermediates. The negative effect of NO is very prominent, inhibiting the N 2 O conversion by strongly occupying the active sites and gradually moving the reaction pathways from N 2 O-CH 4 SCR to NO-assisted N 2 O decomposition, where the former is more efficient than the latter for N 2 O decomposition under the same operation conditions.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…supported noble metals [3][4][5], mixed oxides with different structure [6][7][8][9][10], iron zeolites [11][12][13][14][15], have been investigated for N 2 O decomposition. Supported cobalt catalysts have received considerable attention due to high activity [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%